KESULITAN BELAJAR BIOLOGI DITINJAU DARI KEMAMPUAN AWAL DAN KEMANDIRIAN BELAJAR PADA SISWA KELAS II SEMESTER GASAL SMU NEGERI 4 SURAKARTA TAHUN PELAJARAN 2003/2004 - SRI WIDORETNO; LITHON SUNYOTO; LAYLA NURJANNY (Bioedukasi: Jurnal Pendidikan Biologi, 2005)
The goals of this research were knowing difficulties of biological learning in a point of view of personal pre-academic ability and self-learning processes of second grade of SMUN 4. The research was carried out bycollecting the data by using the ex post facto method. Cluster random sampling technique was used when sampling. Two ways Anava was used to analyze the observed data.The result showed that there are significant impacts of personal pre academic ability, and self-learning processes toward the difficulties of biological learning. Those can be seen from the value of F observed <o, os.-2. 3o>=12,667 > Ftable {0,05:2, 30)-3> 32. Fobserved {0,05:2, 30) ml2,667 > Ftable (0, 05:2, 30) — 3, 32."> The goals of this research were knowing difficulties of biological learning in a point of view of personalpre-academic ability and self-learning processes of second grade of SMUN 4. The research was carried out bycollecting the data by using the ex post facto method. Cluster random sampling technique was used whensampling. Two ways Anava was used to analyze the observed data.The result showed that there are significant impacts of personal pre academic ability, and self-learningprocesses toward the difficulties of biological learning. Those can be seen from the value of F observed <o, os.-2. 3o>=12,667 > Ftable {0,05:2, 30)-3> 32. Fobserved {0,05:2, 30) ml2,667 > Ftable (0, 05:2, 30)— 3, 32.